Cold-Induced Lipoprotein Clearance in Cyp7b1-Deficient Mice - Evangelakos, Ioannis; Kuhl, Anastasia; Baguhl, Miriam; Schlein, Christian; John, Clara; Rohde, Julia K.; Heine, Markus; Heeren, Joerg; Worthmann, Anna (Frontiers in Cell and Developmental Biology, 2022)
Brown adipose tissue (BAT) has emerged as an appealing therapeutic target for cardio metabolic diseases. BAT is a heat producing organ and upon activation substantially lowers hyperlipidemia. In response to cold exposure, not only the uptake of lipoproteins into BAT is increased, but also the Cyp7b1-mediated synthesis of bile acids (BA) from cholesterol in the liver is triggered. Besides their role for intestinal lipid digestion, BA act as endocrine signals that can activate thermogenesis in BAT. When exposed to cold temperatures, Cyp7b1-/- -mice have compromised BAT function along with reduced fecal bile acid levels. Here, we aim to evaluate the role of Cyp7b1 for BAT-dependent lipoprotein clearance. By metabolic studies with radioactive tracers, we show that in response to a cold stimulus, plasma clearance of triglyceride rich lipoproteins (TRL) is reduced into BAT of Cyp7b1-/- mice. The impaired lipid uptake can be explained by reduced lipoprotein lipase (LPL)- levels, which we detected in BAT of Cyp7b1-/- mice. Overall, our findings reveal that alterations of systemic lipoprotein metabolism mediated by cold-activated BAT is dependent, at least in part, on CYP7Β1.